Changes in Gleason Scores for Prostate Cancer: What Should We Expect From a Measurement?. (1st April 2010) - Ramos, Jorge; Uchio, Edward; Aslan, Mihaela; Concato, John
Abstract : Background: Men diagnosed with prostate cancer receive therapy based on various clinical characteristics, including the Gleason score, a measurement (range, 2-10) describing a tumor's histological appearance. An upward shift has occurred in the distribution of Gleason scores during the past decade; this change was influenced by reports suggesting that lower scores (range, 2-4) should not be assigned to biopsy specimens. Methods: We (1) compared Gleason scores from 1994-1995 and 2004-2005 at the same institution, (2) reviewed representative articles examining changes in Gleason scores during the last 2 decades, and (3) assessed the implications of a change in histological measurements. Results: Among men diagnosed with prostate cancer at VA Connecticut, Gleason scores 2 to 4 were reported for 11.4% (19/167) of specimens in 1994-1995 but only 0.4% (1/260) of specimens in 2004-2005; this difference persisted after adjusting for age, clinical stage, and prostate-specific antigen ( P < 0.001). Similar results were evident in previous publications on this topic. A change in criteria for a clinical measurement may have unintended consequences, including problems of inconsistency across "time" and "place." Conclusions: Recent shifts in Gleason scores have led to fewer patients being diagnosed with low-grade prostate cancer; this change can have adverse impacts in clinical care and research.